2018
DOI: 10.1161/hcv.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Radial Artery Access and Best Practices for Transradial Coronary Angiography and Intervention in Acute Coronary Syndrome: A Scientific Statement From the American Heart Association

Abstract: Transradial artery access for percutaneous coronary intervention is associated with lower bleeding and vascular complications than transfemoral artery access, especially in patients with acute coronary syndromes. A growing body of evidence supports adoption of transradial artery access to improve acute coronary syndrome–related outcomes, to improve healthcare quality, and to reduce cost. The purpose of this scientific statement is to propose and support a “radial-first” strategy in the United States for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
302
0
19

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(326 citation statements)
references
References 163 publications
5
302
0
19
Order By: Relevance
“…Transradial artery access (TRA) is associated with lower bleeding and vascular complications and offers major safety advantage over transfemoral artery access . Despite the growing evidence from multiple randomized clinical trials in support of TRA especially in high‐risk patients such as those with acute coronary syndrome (ACS), the adoption of TRA in the United States lags behind compared to Europe and Asia .…”
Section: Introductionmentioning
confidence: 99%
“…Transradial artery access (TRA) is associated with lower bleeding and vascular complications and offers major safety advantage over transfemoral artery access . Despite the growing evidence from multiple randomized clinical trials in support of TRA especially in high‐risk patients such as those with acute coronary syndrome (ACS), the adoption of TRA in the United States lags behind compared to Europe and Asia .…”
Section: Introductionmentioning
confidence: 99%
“…In the RIVAL trial, although radial and femoral approaches led generally to similar outcomes, transradial procedures were associated with less vascular complications . In the MATRIX trial, radial access led to significant reductions in the coprimary composite endpoints of major cardiovascular adverse events and individual endpoints of all‐cause death, major bleeding, and vascular complications . The RIFLE‐STEACS and STEMI‐RADIAL trials complemented these results by showing significant reductions in major bleeding .…”
mentioning
confidence: 95%
“…Radial artery has become the standard access for coronary angiography and percutaneous coronary intervention (PCI) due to several advantages, mainly a significant decrease in vascular complications and bleeding events compared with transfemoral procedures . The recommendation of routine selection of radial access for coronary catheterization results from the growing body of evidence in recent years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A prior survey in 2010 demonstrated that there was significant variation in TRA technique . Since that moment, best practices, recommendations, and evidence for TRA have been developed and disseminated . It is unknown the current use of best practices in TRA around the world to understand knowledge–practice gaps.…”
mentioning
confidence: 99%